Implementasi Doktrin Ultra vires Pada Keabsahan Penyelenggaraan Rapat Umum Pemegang Saham Luar Biasa (RUPS-LB) Perseroan Terbatas - Fateha, Raja Amirah Adha (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2025)
A Limited Liability Company (PT) as a legal entity is regulated by Law Number 40 of 2007 concerning Limited Liability Companies (UUPT), which stipulates the limits of the authority of company organs, including the Extraordinary General Meeting of Shareholders (EGMS). EGMS have a strategic function in making urgent decisions, so their implementation must comply with procedural and substantive provisions in accordance with the UUPT and the Articles of Association. However, practice shows many problems when EGMS are held without complying with applicable legal mechanisms. This study aims to analyze the application of the ultra vires doctrine in assessing the validity of EGMS. The research method used is a normative juridical approach with a statute approach and a case approach, through a literature study of primary, secondary, and tertiary legal materials. The results of the study indicate that the ultra vires doctrine is relevant in two dimensions, namely procedural violations (invalid summons, lack of quorum, abuse of authority by directors) and substantive violations (decisions that deviate from the company's interests or conflict with the UUPT and the Articles of Association). The case study of the Paringin District Court Decision No. 2/Pdt.G/2019/PN.Prn proves that both procedural and substantive violations in the implementation of the Extraordinary General Meeting of Shareholders result in the decision being null and void. Therefore, the implementation of the ultra vires doctrine serves as a legal protection mechanism for shareholders and ensures that the company's strategic decisions remain valid and in line with the principles of corporate propriety.